Synthesis and exploration of structural, optical, magnetic, and electrical properties of Ti-doped Mn–Ni–Zn ferrite - Md. Arman Hossain; Hasan Khaled Rouf; Murad Hossain; Mohammad Khurshed Alam; Mohammed Nazrul Islam Khan (AIP Advances)
Mn0.5Ni0.1Zn0.4TixFe2−xO4 (x = 0.00, 0.03, 0.05, 0.07, 0.10) was synthesized using the solid-state reaction method to analyze the effects of titanium substitution on its structural, optical, magnetic, and electrical properties. Characterization techniques employed include x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible (UV–vis) spectroscopy, PPMS, and an impedance analyzer. Rietveld refinement of the XRD data confirms that the samples adopt a spinel cubic structure (Fd3̄m space group) with the presence of secondary Fe2O3 peaks across all Ti-doped samples. The lattice parameter shows an increasing trend with an increase in Ti content. The theoretical density (ρth) and bulk density (ρB) findings reveal that ρth exceeds ρB, suggesting that pores are formed within the bulk specimens. The FTIR spectrum displays peaks at 357 and 529 cm−1, confirming the formation of metal oxide bonds at both tetrahedral and octahedral sites. UV–vis spectroscopy shows significant absorption in the UV region between 200 and 240 nm. The Tauc plot analysis reveals that the bandgap energy increases with higher Ti content. The study of the magnetic hysteresis loop shows a decrease in saturation magnetization (Ms) as Ti4+ content rises, likely due to the transition of Fe3+ ions from octahedral to tetrahedral sites and the non-magnetic nature of titanium. In addition, the dielectric constant and dielectric loss tend to decrease with increasing frequency, while resistivity increases with higher Ti concentrations. Notably, the 5% Ti doping sample exhibited high resistivity and low dielectric loss at elevated frequencies, indicating promising potential for high-frequency applications.